A Multifunctional Nanoplatform Based on Graphene Quantum Dots‐Cobalt Ferrite for Monitoring of Drug Delivery and Fluorescence/Magnetic Resonance Bimodal Cellular Imaging. Issue 10 (14th July 2022) - Teng, Yun; Yuan, Shuai; Shi, Jue; Pong, Philip W. T.
Abstract : A novel multifunctional nanoplatform based on graphene quantum dots (GQDs)‐cobalt ferrite (CoFe2 O4 ) is demonstrated for monitoring of the drug delivery and fluorescence/magnetic resonance imaging (MRI) bimodal cellular imaging. The nanoplatform is fabricated by assembling the GQDs onto the surface of magnetic CoFe2 O4 @SiO2 (CFO@SiO2 ) via covalent binding, subsequently conjugated with folic acid (FA). Then anticancer drug doxorubicin (DOX) is loaded on the GQD‐CFO/SiO2 /FA with a capacity of 65.4 wt%. The DOX/GQD‐CFO@SiO2 /FA can be used for monitoring of drug release by detecting the Förster resonant energy transfer (FRET) signals, with the GQDs serve as the drug carrier and the donor in FRET model. Herein, the monitoring of drug delivery is explored via the corresponding changes in FRET. The reduced brightness of T 2 ‐weighted MRI images indicates the potential of GQD‐CFO@SiO2 /FA to be applied as the negative contrast agent. The fluorescence/MRI bimodal cellular imaging can facilitate the transportation of drug delivery. Furthermore, the cytotoxicity assay confirms the desirable biocompatibility of GQD‐CFO@SiO2 /FA nanoplatform, and DOX/GQD‐CFO@SiO2 /FA exhibits notable cytotoxicity to HeLa cells. These results demonstrate the significantly increased therapeutic efficiency of this nanoplatform. Thus, the novel GQD‐CFO@SiO2 /FA can be a promising multifunctional nanoplatform with monitoring of drug delivery and fluorescence/MRI bimodal cellular imaging. Abstract : Graphene quantum dots (GQDs)‐cobalt ferrite (CoFe2 O4 ) is widely used for both drug delivery monitoring and fluorescence/magnetic resonance bimodal cellular imaging. Herein, a multifunctional nanoplatform based on GQDs‐CoFe2 O4 is developed to perform drug delivery and cellular imaging simultaneously. Cytotoxicity assay confirms the desirable biocompatibility of the nanoplatform with notable cytotoxicity to HeLa cells, demonstrating its significantly increased therapeutic efficiency.